2022
DOI: 10.3389/fpubh.2022.804546
|View full text |Cite
|
Sign up to set email alerts
|

Is Teachers' Depression Contagious to Students? A Study Based on Classes' Hierarchical Models

Abstract: BackgroundAccording to the theory of emotional contagion, emotions in one person can trigger similar emotions in groups within social networks. In schools, the class just like a small social network, that teachers' emotion, such as depression, might be contagious to their students. However, until now there is few studies reporting this issue. This study aims to explore whether teachers' depression be contagious to students and what mechanics behind the phenomenon.MethodsUsing Children's depression and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Studies have also shown that teachers suffering from depression can adversely affect students. Wu and Lu (2022) found that teachers' depression can negatively affect students' academic achievement and emotional well-being. Thus, schools and educational institutions must prioritize teachers' psychological well-being to ensure positive outcomes for teachers and students.…”
Section: Psychological Well Beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that teachers suffering from depression can adversely affect students. Wu and Lu (2022) found that teachers' depression can negatively affect students' academic achievement and emotional well-being. Thus, schools and educational institutions must prioritize teachers' psychological well-being to ensure positive outcomes for teachers and students.…”
Section: Psychological Well Beingmentioning
confidence: 99%
“…Second, teachers strongly influence their students by virtue of their profession. Their low well-being can hamper the well-being and learning of the students (Roeser et al, 2022;Wu and Lu, 2022). Thus, the study is vital in any geographical context to understand the measures that can be taken to enhance teachers' psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been studies on teacher, few have specifically examined teachers' mental health and welfare during unprecedented events like the COVID-19 pandemic. Ideally, supporting teacher well-being would involve ensuring adequate salaries and benefits, manageable workloads, professional development opportunities, and support from employers and the government (Wu and Lu, 2022). However, the current situation in Vietnam falls short of this ideal, with many teachers facing challenges such as low salaries, heavy workloads, and limited support, leading to high-stress levels and burnout (Hoang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%